2019
DOI: 10.1016/j.mechmachtheory.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Variable stiffness ankle actuator for use in robotic-assisted walking: Control strategy and experimental characterization

Abstract: Despite the increasing interest in using powered ankle-foot orthoses for assistive purposes, their development and benchmarking still present core challenges. Powered orthoses have to be safe and provide adequate torque while keeping limited size and weight. The discordance of these requirements is a challenge for the development of these devices. This paper describes the control strategy and characterization of a compact variable stiffness actuator, to be used in an assistive ankle-foot orthosis for impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 61 publications
0
38
0
Order By: Relevance
“…The influence of this parameter on the actuator's performance has been already shown in several test-bench experiments [37,40]. In [37] it was shown that no single stiffness level of the ankle actuator used in the MAPO could be defined as optimal based on the actuator's torque tracking performance, due to the dependence of the benefits of a specific actuator's stiffness level on both the assistive torque reference and the user's ankle kinematics. However, the effect of the actuator's stiffness level on the users has not been yet studied.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The influence of this parameter on the actuator's performance has been already shown in several test-bench experiments [37,40]. In [37] it was shown that no single stiffness level of the ankle actuator used in the MAPO could be defined as optimal based on the actuator's torque tracking performance, due to the dependence of the benefits of a specific actuator's stiffness level on both the assistive torque reference and the user's ankle kinematics. However, the effect of the actuator's stiffness level on the users has not been yet studied.…”
Section: Introductionmentioning
confidence: 95%
“…1. The design and characterization of the MACCEPA-based ankle actuator implemented in the MAPO have been already presented in detail in [37,38]. Briefly, the ankle VSA is used to actuate the MAPO in both directions of the sagittal plane (Additional file 1).…”
Section: Mapo Hardware and Control Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…In the current research field of the flexible robot, variable stiffness joint (VSJ) is a kind of flexible robot actuation joint with independent and controllable characteristics of position and stiffness [1]. The inherent flexibility (affected by the internal elastic elements of the joint) and the adjustability of the joint output stiffness make the VSJ suitable for physical human-robot interaction applications such as the roboticassistive devices [2,3], exoskeleton robot [4], prosthetic joint [5], wearable devices [6,7], etc. When the VSJ is used as the actuated joint of the rehabilitation training robot, the therapist can adjust the joint stiffness of the robot according to the patients' rehabilitation training process.…”
Section: Introductionmentioning
confidence: 99%